2010
DOI: 10.1080/14697680902946514
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of energy storage: an optimal switching approach

Abstract: We consider the valuation of energy storage facilities within the framework of stochastic control. Our two main examples are natural gas dome storage and hydroelectric pumped storage. Focusing on the timing flexibility aspect of the problem we construct an optimal switching model with inventory. Thus, the manager has a constrained compound American option on the inter-temporal spread of the commodity prices.Extending the methodology from Carmona and Ludkovski (2008), we then construct a robust numerical scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
120
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 27 publications
0
120
0
Order By: Relevance
“…See for example [30,3]. Moreover, some of these methods have been extended to value gas storage and we refer the interested reader to [28,27,50,77]. and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…See for example [30,3]. Moreover, some of these methods have been extended to value gas storage and we refer the interested reader to [28,27,50,77]. and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…The investment value of the battery when used as reserve capacity is therefore equal to the value of an infinite sequence of such real options, which we call the 'lifetime valuation' (a somewhat related study may be found in Carmona and Ludkovski (2010), where the value of gas storage units used for price arbitrage is derived using a numerical approach). We show that the lifetime value is finite when the sum of the single contract payments (initial premium and reward) is strictly less than the imbalance price upon exercise.…”
Section: Resultsmentioning
confidence: 99%
“…However, our approach is more general than the one of LMS. We also introduce new ADPs, adding to the literature on commodity storage valuation (e.g., Chen and Forsyth 2007, Boogert and De Jong 2008, Thompson et al 2009, Carmona and Ludkovski 2010, Secomandi 2010, Wu et al 2010, Birge 2011, Boogert and De Jong 2011, and Felix and Weber 2012. More broadly, our PSR approach potentially provides a solution methodology for other real option problems.…”
Section: Literature Reviewmentioning
confidence: 99%